2022
DOI: 10.14444/8295
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Fat Thickness on Erect Radiographs Is a Predictor of Infection Following Elective Posterior Lumbar Fusion

Abstract: Background: Posterior lumbar fusions are a common and successful procedure, yet surgical site infection (SSI) is still prevalent and causes significant morbidity. Obesity is a well-established risk factor for SSI. Still, the accuracy of the body mass index (BMI) caused some to suggest other metrics that are more representative of the thickness of the soft-tissue envelope in the surgical site.Methods: A retrospective review of all cases that developed SSI following posterior lumbar fusion over the past 5 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…They found BMI and soft tissue depth to be significantly associated with SSI. [ 19 ] In another study on patients undergoing lumbar spine procedures through a midline posterior approach, there was a 6% increased risk of infection for every 1 mm thickness of subcutaneous fat (measured on magnetic resonance imaging), as well as a 4-fold increase in risk of infection with greater than 50 mm of posterior lumbar back fat thickness. [ 9 ] This has also been proven in patients who underwent posterior cervical spine fusion.…”
Section: Discussionmentioning
confidence: 99%
“…They found BMI and soft tissue depth to be significantly associated with SSI. [ 19 ] In another study on patients undergoing lumbar spine procedures through a midline posterior approach, there was a 6% increased risk of infection for every 1 mm thickness of subcutaneous fat (measured on magnetic resonance imaging), as well as a 4-fold increase in risk of infection with greater than 50 mm of posterior lumbar back fat thickness. [ 9 ] This has also been proven in patients who underwent posterior cervical spine fusion.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is an insufficient number of studies internationally and only one to our knowledge nationally that studied the correlation between lumbar fat thickness and SSI. In the national study that was published in the International Journal of Spine Surgery on July 2022, they reported a significant association of SSI with subcutaneous fat thickness measured on erect radiographs 16 . Another multicenter research assessed adipose index correlation with deep SSI and concluded that increased adipose tissue is an independent risk that was significantly associated with developing deep SSI.…”
Section: Discussionmentioning
confidence: 99%